Mapping the Linguistic Politeness of Dusun Tangkuru Society: The Pattern of Politeness in Makassar - Tanasy, Novalia; Nasir, A. Muhajir; Yulianti, Nur Indah Rara (Universitas Lancang Kuning, 2020)
This study aims to reveal events or facts, circumstances, phenomena, variables and circumstances that occur during the research by presenting what actually happened and know the politeness of the language used by Dusun Tangkuru society when interacting with Makassar society. This research uses a descriptive qualitative research method, with a form of descriptive data presentation. Data obtained through the interview process. The data source is taken from Dusun Tangkuru society. Based on the results of research on mapping the language politeness of Dusun Tangkuru society towards Makassar language, it was found that there was a level of politeness used by the Tangkuru hamlet community. Not only that, the researchers also found that there were factors that influenced the pattern of politeness of Dusun Tangkuru society towards Makassar language which could be caused by social factors such as stratification, distance and kinship.